Studi Sebaran Karakteristik Kualitas Air dengan Parameter BOD, COD, DO, NH3-N, TSS, dan pH di Waduk Sutami - Nathania, Nadya Ayu; Sayekti, Rini Wahyu; Sholichin, Moh. (Fakultas Teknik, Universitas Brawijaya, 2021)
Sutami Reservoir is a multipurpose reservoir with a water supply from Brantas River. The problem that occurs in the Brantas River is the decline in water quality due to the high discharge of agricultural, domestic, and industrial waste. The purpose of this study is to determine the distribution of water quality in 2015-2020 for the dry season using the Pollution Index, determine the regression model that best suits the variation of the pollution index value, and determine the pollution load capacity for Total-P in 2016 based on its trophic status. This research was conducted at the Upper, Middle, and Downstream Monitoring Stations at depths I (0.3 m), II (5 m), and III (10 m) for parameters BOD, COD, DO, NH3-N, TSS, and pH. From this study, it was found that the distribution of water quality of the Sutami Reservoir in 2015-2020 was classified as lightly polluted with the most appropriate regression model, namely the polynomial regression model. By comparing the pollution load capacity for Total-P in 2016 with the level of Total-P that enter the Sutami Reservoir, it was found that the level of Total-P that entered in the Sutami Reservoir had exceeded its proper capacity.Â Waduk Sutami merupakan waduk multiguna dengan pasokan air dari Sungai Brantas. Permasalahan yang terjadi di Sungai Brantas yaitu menurunnya kualitas air akibat tingginya buangan limbah pertanian, domestik, dan industri. Tujuan dari penelitian ini yaitu untuk menentukan sebaran karakteristik kualitas air dimusim kemarau tahun 2015-2020 dengan menggunakan Metode Indeks Pencemaran, menentukan model regresi yang paling sesuai dengan variasi nilai indeks pencemaran, serta menentukan daya tampung beban pencemaran Total-P tahun 2016 berdasarkan status trofiknya. Penelitian ini dilakukan pada Stasiun Monitoring Waduk Sutami Hulu, Tengah, dan Hilir pada kedalaman I (0.3 m), II (5 m), dan III (10 m) untuk parameter BOD, COD, DO, NH3-N, TSS dan pH. Dari penelitian ini didapatkan hasil sebaran karakteristik kualitas air Waduk Sutami tahun 2015-2020 tergolong tercemar ringan dengan model regresi yang paling sesuai yaitu model regresi polinomial. Dengan membandingkan nilai daya tampung beban pencemaran Total-P tahun 2016 dengan kadar yang masuk ke Waduk Sutami didapatkan bahwa kadar Total-P yang masuk ke Waduk Sutami telah melebihi daya tampung yang seharusnya.